Involving women in personalised decision‐making on mode of delivery after caesarean section: the development and pilot testing of a patient decision aid. (January 2014) - Schoorel, ENC; Vankan, E; Scheepers, HCJ; Augustijn, BCC; Dirksen, CD; de, M; van, SMJ; Kwee, A; Melman, S; Nijhuis, JG; Aardenburg, R; de, K; et al.
<x xml:space="preserve">Abstract</x> Objective To develop a patient decision aid (PtDA) for mode of delivery after caesarean section that integrates personalised prediction of vaginal birth after caesarean (VBAC) with the elicitation of patient preferences and evidence‐based information. Design A PtDA was developed and pilot tested using the International Patients Decision Aid Standards (IPDAS) criteria. Setting Obstetric health care in the Netherlands. Population A multidisciplinary steering group, an expert panel, and 25 future users of the PtDA, i.e. women with a previous caesarean section. Methods The development consisted of a construction phase (defini‐tion of scope and purpose, and selection of content, framework, and format) and a pilot testing phase by interview. The process was supervised by a multidisciplinary steering group. Main outcome measures Usability, clarity, and relevance. Results The construction phase resulted in a booklet including unbiased balanced information on mode of birth after caesarean section, a preference elicitation exercise, and tailored risk information, including a prediction model for successful VBAC. During pilot testing, visualisation of risks and clarity formed the main basis for revisions. Pilot testing showed the availability of tailored structured information to be the main factor involving women in decision‐making. The PtDA meets 39 out of 50 IPDAS criteria (78%): 23 out of 23 criteria for content (100%) and 16 out of 20 criteria for the development process (80%). Criteria for effectiveness (n = 7) were not evaluated. Conclusions An evidence‐based PtDA was developed, with the probability of successful VBAC and the availability of structured information as key items. It is likely that the PtDA enhances the quality of decision‐making on mode of birth after caesarean section.